2017
DOI: 10.1039/c7ay01616f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of lithium in scalp hair by time-of-flight secondary ion mass spectrometry with high energy (MeV) primary ions

Abstract: The application of MeV-SIMS is presented for the detection and mapping of lithium in chemically unprocessed, longitudinally sectioned scalp hair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Since hair sample measurements is normally 1 hour, the hair chemical environment and morphology should remain unchanged. Scanning electron micrograph images further confirmed that the morphology of the analyzed samples remained unaltered after 1 hour of measurement with MeV-SIMS [53]. With particle-induced X-ray emission, however, a clear change in the sample's physical appearance can be noted when measuring for a longer time frame.…”
Section: Ion Beam Methods and Synchrotron-based Techniques In Hair Elmentioning
confidence: 49%
See 3 more Smart Citations
“…Since hair sample measurements is normally 1 hour, the hair chemical environment and morphology should remain unchanged. Scanning electron micrograph images further confirmed that the morphology of the analyzed samples remained unaltered after 1 hour of measurement with MeV-SIMS [53]. With particle-induced X-ray emission, however, a clear change in the sample's physical appearance can be noted when measuring for a longer time frame.…”
Section: Ion Beam Methods and Synchrotron-based Techniques In Hair Elmentioning
confidence: 49%
“…Another example includes the use of ion beam or synchrotron radiation analysis in epidemiological and etiological studies assessing exposure to toxic metals in vulnerable populations [14]. A recent exploratory study also pointed to the use of MeV-SIMS for the detection and mapping of the micronutrient lithium and its isotopes in longitudinally sectioned hair [53]. Lithium is an important psychopharmaceutical in the psychiatric community, and since it is quite challenging detecting the low Z element lithium that is present at trace levels in biological tissues, such analysis may find important application in monitoring medication adherence among psychiatric patients using hair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the samples should be prepared very thin (3-5 μm) to enable the penetration of the swift primary ions to the CEM detector, the continuous primary mode MeV-SIMS is not applicable on specific materials, i.e. human hair [29].…”
Section: Introductionmentioning
confidence: 99%